Uji Aktivitas Antioksidan Ekstrak Beberapa Jenis Bunga dengan Metode DPPH (1,1-diphenyl-2-picrylhydrazil) - munira, munira; Nasir, Muhammad; Halimatussakdiah (JURNAL ILMIAH FARMASI SIMPLISIA, 2024)
Several ornamental plants such as roses (Rosa sp.), hibiscus flowers (Hibiscus rosa-sinensis) and butterfly pea flowers (Clitoria ternatea) function as medicinal ingredients. These flowers have varying colors. The varying colors of these flowers are caused by anthocyanin compounds which are part of the secondary metabolites of flavonoids. Flavonoids are part of the group of phenolic compounds and flavonoids have the ability to act as antioxidants. This research aims to determine the antioxidant activity levels of rose, hibiscus and butterfly pea flower extracts. This research is experimental. Extraction was carried out by maceration using 70% ethanol solvent. Determination of the antioxidant activity test using the DPPH (1,1-diphenyl-2-picrylhydrazil) free radical scavenging method which was measured using a UV-Vis spectrophotometer. The results of the antioxidant activity test showed that rose flower extract had an IC50 value of 18.39 µg/ml and hibiscus flowers had an IC50 value of 3.56 µg/ml and butterfly pea flower had an IC50 value of 9.44 µg/ml. Hibiscus flowers have higher antioxidant activity than roses and butterfly pea flowers.